2023
DOI: 10.7759/cureus.37557
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram Interpretation Competency of Medical Interns in Saudi Arabia: A Cross-Sectional Study

Abstract: To determine the competence of medical interns in Saudi Arabia in interpreting common ECG abnormalities, explore limitations, and facilitate solutions to the development of ECG interpretation skills in Saudi Arabia. MethodsThis cross-sectional study was conducted from 11 June 2022 to 3 November 2022 using the convenience stratified sampling technique among 373 medical interns (54.4% male and 45.6% female) in 15 medical colleges within Saudi Arabia. ResultsAlmost all (91.7%) of the participants recognized the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…A study done at one of the medical schools in Poland also demonstrated that medical students have a good level of competency in interpreting normal ECG, but they lack the desired competency level to interpret abnormal ECG [5]. Another study by Jablonover et al and Al Mousa et al also showed a similar result among medical students [6,7].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A study done at one of the medical schools in Poland also demonstrated that medical students have a good level of competency in interpreting normal ECG, but they lack the desired competency level to interpret abnormal ECG [5]. Another study by Jablonover et al and Al Mousa et al also showed a similar result among medical students [6,7].…”
Section: Discussionmentioning
confidence: 87%
“…A study done at a medical school in New Zealand among finalyear medical students and residents did not achieve the required competency to interpret different clinical conditions in ECG [1]. This trend was seen across the globe in various other studies [4][5][6][7]. A meta-analysis by Cook et al found that physicians at all levels had deficiencies in interpreting ECG [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across 427 medical students from Umm Al-Qura University, Saudi Arabia, the ventricular extrasystole and pathological Q wave were not identified by nearly 75.1% of the participants [ 15 ]. Medical interns were also not able to correctly diagnose patients with such rhythms (75.7%) in a study carried out across 14 medical universities in Saudi Arabia [ 16 ]. Conversely, our finding differs from that reported in the Iran region.…”
Section: Discussionmentioning
confidence: 99%